2020
DOI: 10.3389/fpsyg.2020.01470
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Social Entrepreneurial Organizations: An Empirical Study of Teacher–Student Co-entrepreneurship

Abstract: This paper explores the impact of different types of social entrepreneurship education cultivation models on students' opinion on social entrepreneurship, defines and classifies the emerging social entrepreneurship cultivation models in colleges and universities, and confirms the performance difference between the teacher-student coentrepreneurship (TSCE) cultivation model and the traditional cultivation model through quantitative research. Chi-square analysis and the structural equation model are used to veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The objective of college social and political education (SPE) is to improve the social, political, and moral qualities of teachers and students through certain social concepts, political views, and ethical norms education ( Du et al, 2020 ; Li et al, 2020 ; Wu A. et al, 2020 ). College SPE has a particular practical significance by providing solid support for the critical force of China’s economic construction, college entrepreneurs, IEE, and sports ( Mu et al, 2020 ; Philpot et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The objective of college social and political education (SPE) is to improve the social, political, and moral qualities of teachers and students through certain social concepts, political views, and ethical norms education ( Du et al, 2020 ; Li et al, 2020 ; Wu A. et al, 2020 ). College SPE has a particular practical significance by providing solid support for the critical force of China’s economic construction, college entrepreneurs, IEE, and sports ( Mu et al, 2020 ; Philpot et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is supported by the study conducted in the United States, Germany, and Saudi Arabia, stating that the objectives, methods, and organizational structures of entrepreneurship education were formed by preparing schools' autonomy in relation to societal imaginaries (Al-Mamary & Alshallaqi, 2022;Wadhwani & Viebig, 2021). However, this finding needs attention from other studies in China found that mostly a high level of organizational dedication and commitment results from a high level of team member trust, and culture (Du et al, 2020;Lyu et al, 2021). Therefore, instead of simply establishing an entrepreneurship program, schools need to ensure this high level of trust in the team for teachers or students interested in innovation or entrepreneurship in groups to ensure good operating performance of the entrepreneurship program.…”
Section: Discussionmentioning
confidence: 67%
“…For teachers and students, this relationship does not necessarily aim at entrepreneurship but can be a partnership. Therefore, Du et al work on the traditional cultivation model and propose the teacher-student co-entrepreneurship cultivation model, which refers to collaborative innovation or collaborative entrepreneurship between teachers and students [64]. Although there have been studies focusing on the interaction between teachers and students in the entrepreneurship process [65], at present the focus on co-creation is relatively scarce in entrepreneurship education and research.…”
Section: Co-creation Strategymentioning
confidence: 99%